2021
DOI: 10.1111/petr.14131
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, risk factors, and outcomes of neutropenia after liver or kidney transplantation in children

Abstract: Background: While prior adult studies have shown that approximately 20%-38% of subjects undergoing solid-organ transplant develop neutropenia, similar analyses in pediatric subjects are scarce. Methods:We conducted a retrospective chart review of liver transplant (LT) and kidney transplant (KT) recipients at our center during the period 2008-2018. All of the KT and none of the LT subjects during this time period had induction with either anti-thymocyte globulin (ATG) or basiliximab at time of transplant. Neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Previous studies in adults demonstrate a rate of 6-8% severe PTNs [10,16,22]. These nding are consistent with the suggestion of Jarasvaraparn et al, that children have a higher incidence and a higher rate of severe episodes of PTN when compared to adults [21]. Possible explanations for the increased incidence and severity of neutropenia in pediatric KTRs include higher serum concentrations of medications known to cause bone marrow suppression without available tests for drug levels, increased sensitivity of the bone marrow to suppressive effects of medications and/or infections, and a higher incidence of viral infections in pediatric solid-organ transplant recipients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies in adults demonstrate a rate of 6-8% severe PTNs [10,16,22]. These nding are consistent with the suggestion of Jarasvaraparn et al, that children have a higher incidence and a higher rate of severe episodes of PTN when compared to adults [21]. Possible explanations for the increased incidence and severity of neutropenia in pediatric KTRs include higher serum concentrations of medications known to cause bone marrow suppression without available tests for drug levels, increased sensitivity of the bone marrow to suppressive effects of medications and/or infections, and a higher incidence of viral infections in pediatric solid-organ transplant recipients.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of any PTN was 60% (53 patients out of 89 KTRs) which is consistent with Becker-Cohen's ndings, which demonstrated a 64% prevalence of pediatric PTN in a mean follow up time of 4.4 years [27]. Another study on pediatric KTRs demonstrated a prevalence of 54.8% of PTN during the rst follow up year, using a stricter threshold for de ning neutropenia as ANC ≤ 1000 [21]. Both studies included similar cohort sizes relative to our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A systematic review of cancer patients has demonstrated that primary support with C‐CSF is associated with 7% lower all‐cause mortality 20 . In the field of KT several idiosyncratic medication interactions and CMV infection can cause neutropenia and clinicians experience complex management dilemmas 1,3–11 . The most common strategy to treat neutropenia is to reduce maintenance immunosuppression, however, G‐CSF use is increasingly reported.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] CMV does not typically cause neutropenia in immunocompetent individuals but is a component of the CMV syndrome that includes fever, malaise, atypical lymphocytosis, leukopenia, thrombocytopenia, and/or elevated hepatic transaminases as well as symptomatic end-organ disease. 14,50 High-risk CMV serostatus has been associated with risk of neutropenia in a cohort of 100 pediatric kidney and liver transplant recipients 56 as well as large cohorts of adult liver, kidney, and heart recipients, 30,57,58 although it can be difficult to separate the effects of CMV serostatus from those of prophylactic valganciclovir.…”
Section: Ta B L E 1 Classification Of Severity Of Neutropeniamentioning
confidence: 99%